Penalaan PSS pada Sistem Generator Tenaga Menggunakan Algoritma Penyerbukan Bunga - Muhammad Ruswandi Djalal; Sonong Sonong (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This research proposed a tuning method of power system stabilizer (PSS) using an intelligent method based on flower pollination algorithm (FPA) on Pajalesang generator located in Soppeng district. The observed result is the deviation response of velocity and rotor angle in case of disturbance. The case study used as the disturbance to this generator system is a load addition of 0.05 pu. The results show that velocity deviation response without PSS is 0.01152 pu to -0.0248 pu, using PSS trial is 0.007014 pu to -0.02174 pu, using PSS bat algorithm is 0.003972 pu to -0.01865 pu, and using the proposed method of PSS flower algorithm is 0.002149 pu to -0.01678 pu. The rotor angle response shows better results with reduced oscillation and rapidly leading to the steady-state condition. The performance of Pajalesang diesel power plant increased with the installation of FPA PSS, with parameters respectively Kpss=8.5956, T1= 0.0247, T2=0.2484, T3=0.4776, and T4=0.8827.